2005
DOI: 10.1381/0960892053268264
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Deficiencies following Bariatric Surgery: What Have We Learned?

Abstract: Deficiencies in vitamins and other nutrients are common following the Roux-en-Y gastric bypass (RYGBP), biliopancreatic diversion (BPD) and biliopancreatic diversion with duodenal switch (BPDDS), and may become clinically significant if not recognized and treated with supplementation. This paper presents a review of the current literature and evidence of the most commonly deficient vitamins and minerals following weight loss surgery, including protein, iron, vitamin B12, folate, calcium, the fat-soluble vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
231
0
64

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(302 citation statements)
references
References 35 publications
7
231
0
64
Order By: Relevance
“…1 However, laboratory studies of iron deficiency usually show a microcytosis, whereas macrocytes predominated on our patient's peripheral smear, making iron deficiency an unlikely explanation for her anemia. Autoimmune hemolytic anemia is due to the development of IgG or IgM antibodies that react with protein antigens on the red blood cell surface.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…1 However, laboratory studies of iron deficiency usually show a microcytosis, whereas macrocytes predominated on our patient's peripheral smear, making iron deficiency an unlikely explanation for her anemia. Autoimmune hemolytic anemia is due to the development of IgG or IgM antibodies that react with protein antigens on the red blood cell surface.…”
mentioning
confidence: 57%
“…Their deficiencies lead to megaloblastic anemia, which at this point is the most likely diagnosis for this patient. 1 The patient was admitted for blood transfusions and further work-up. A review of systems revealed that she had begun to become "clumsy" during the past 2 years.…”
mentioning
confidence: 99%
“…Some authors suggested that neurological complications following bariatric surgery were due to disturbed protein and vitamin metabolism (10). Deficiencies of iron, zinc, cobalamine (B12), thiamine (B1) and fat-soluble vitamins such as A, D, E, K were determined (10).…”
Section: Discussionmentioning
confidence: 99%
“…While research has shown successful treatment outcomes with intravenous iron replacement, clinical guidelines for post-RYGB administration of intravenous iron preparations vary considerably and access to intravenous iron replacement may be limited in the primary care setting because of: (a) delayed recognition of the severity of the deficiency; (b) a lack of consistent diagnostic criteria, indications, and optimal treatment goals; (c) provider concerns related to potential adverse effects of intravenous iron preparations; and (d) access to infusion centers for monitored treatments (Bailie, 2012;Bloomberg, Fleishman, Nalle, Herron, & Kini, 2005;DeFilipp et al, 2013;Malone, Alger-Mayer, Lindstrom, & Bailie, 2013;von Drygalski & Andris, 2009). …”
Section: Clinical Presentationmentioning
confidence: 99%